Pengembangan Model Literasi Berbasis Kearifan Lokal Sebagai Upaya Peningkatan Minat Baca Siswa di SDN 025 Samarinda Utara - Euis Kusumarini; Eka Selvi Handayani; Ana Fajar Wati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This community service program aims to develop a local wisdom-based literacy model as an effort to improve students’ reading interest at SD Negeri 025 Samarinda Utara. The low level of reading interest among elementary school students remains a challenge in the implementation of the School Literacy Movement initiated by the Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi. One of the contributing factors is the lack of contextual reading materials that are relevant to students’ socio-cultural environment. Therefore, integrating local wisdom into literacy activities is considered an innovative strategy to enhance students’ engagement in reading activities.The implementation method included needs analysis, the design of a literacy model, program implementation through storytelling of East Kalimantan folktales, the development of a culturally themed reading corner, and teacher mentoring in integrating literacy into classroom learning. Evaluation was conducted through observation of student participation, reading interest questionnaires, and reflective discussions with teachers.The results indicate an increase in students’ enthusiasm for reading activities, a higher frequency of classroom reading corner utilization, and improved understanding of local cultural values. The local wisdom-based literacy model proved effective in creating a contextual, engaging, and meaningful learning atmosphere. This program is expected to serve as a sustainable model for strengthening literacy culture in elementary schools.